CRIMINAL LAW POLICY ON THE DERADICALIZATION OF CRIMINAL ACTS OF TERRORISM - H.Yusep Mulyana (Badan Penerbit STIEPARI Press, 2023)
The criminal law policies currently being implemented in the context of combating terrorism in Indonesia include the implementation of the Law on Criminal Acts of Terrorism, the Law on the Eradication and Prevention of the Financing of Terrorism and the Emergency Law on Firearms. Policies for the formulation of criminal law in the future include making changes to the bill on counter terrorism, especially in article 1 by including deradicalization programs, deideology into the bill, as well as changing, adding and inserting several articles into several Laws for Combating Criminal Acts of Terrorism. , which can be applied through a political approach that focuses on the factors causing terrorism. The obstacle to the implementation of deradicalization as an effort to prevent terrorism in Indonesia is that deradicalization is a preventive effort to tackle terrorism. In carrying out the deradicalization, the main actors face obstacles, including: Facilities and Infrastructure Factors, Minimal Officers and the uncooperative nature of prisoners, ex-convicts or radical community groups.